2020
DOI: 10.1101/2020.06.10.144634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relating Bone Strain to Local Changes in Radius Microstructure Following 12 Months of Axial Forearm Loading in Women

Abstract: 18Work in animal models suggest that bone structure adapts to local bone strain, but this 19 relationship has not been comprehensively studied in humans. Here, we quantified the 20 influence of strain magnitude and gradient on bone adaptation in the forearm of 21 premenopausal women performing compressive forearm loading (n=11) and non-22 36 normal loads and in response to a novel loading intervention, and represents an 37 important step toward defining exercise interventions to maximize bone strength. 38 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Consistent with previous studies which found normal physiological activity levels result in significant relationships between bone formation and FE-derived mechanical stimulus 30 , 31 , the mechanoregulation analysis revealed strong relationships between local mechanics and remodeling in all groups. Trends were observed in the magnitude of the difference between the resorption and formation threshold values (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies which found normal physiological activity levels result in significant relationships between bone formation and FE-derived mechanical stimulus 30 , 31 , the mechanoregulation analysis revealed strong relationships between local mechanics and remodeling in all groups. Trends were observed in the magnitude of the difference between the resorption and formation threshold values (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…However, the regional and tissue-level measures do not fully capitalize on the capabilities of HR-pQCT, which when combined with a longitudinal imaging protocol include microstructural analysis of bone remodeling 29 through dynamic morphometry which allows for the direct quantification of bone formation and resorption and of the association of this remodeling with the mechanical loading of the bone, i.e. mechanoregulation 30,31 . To date, the ability of such longitudinal, extended HR-pQCT analysis tools to detect clinically relevant changes in bone quality and quantity has yet to be thoroughly investigated.…”
mentioning
confidence: 99%
“…Consistent with previous studies which found normal physiological activity levels result in significant relationships between bone formation and FE-derived mechanical stimulus 31,32 , the mechanoregulation analysis revealed strong relationships between local mechanics and remodeling in all groups. Differences were observed in the magnitude of the difference between the resorption and formation threshold values (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Further, the ability to track changes in the cortical and trabecular compartments has revealed both age-related 2426 and disease-specific characteristics 2629 not previously realized using regional DXA-based measures. However, the regional and tissue-level measures do not fully capitalize on the capabilities of HR-pQCT, which when combined with a longitudinal imaging protocol include microstructural analysis of bone remodeling 30 and mechanoregulation 31,32 . To date, the ability of such longitudinal, extended HR-pQCT analysis tools to detect clinically relevant changes in bone quality and quantity has yet to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that a similar mechanical loading regimen elicited changes in distal radius BMD that were related to local mechanical strain environment ( Bhatia et al, 2015 ). In a subset of this cohort, we showed that local trabecular strain magnitude and gradient were higher near formation versus resorption sites ( Mancuso and Troy, 2020 ). Similarly, local trabecular strain environment has been linked to local formation/resorption in small animals ( Webster et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%